Salt-specific effects in lysozyme solutions - Janc, T.; Kastelic, M.; Bončina, M.; Vlachy, V. (Condensed Matter Physics, 2016)
The effects of additions of low-molecular-mass salts on the properties of aqueous lysozyme solutions are examined by using the cloud-point temperature, Tcloud, measurements. Mixtures of protein, buffer, and simple salt in water are studied at pH=6.8 (phosphate buffer) and pH=4.6 (acetate buffer). We show that an addition of buffer in the amount above Ibuffer = 0.6 mol dm⁻³ does not affect the Tcloud values. However, by replacing a certain amount of the buffer electrolyte by another salt, keeping the total ionic strength constant, we can significantly change the cloud-point temperature. All the salts de-stabilize the solution and the magnitude of the effect depends on the nature of the salt. Experimental results are analyzed within the framework of the one-component model, which treats the protein-protein interaction as highly directional and of short-range. We use this approach to predict the second virial coefficients, and liquid-liquid phase diagrams under conditions, where Tcloud is determined experimentally. Ефекти додавання солей з малою молекулярною масою на властивостi водних розчинiв лiзозиму встановлюються з вимiрювань температури точки хмари, Tcloud. Дослiджуються сумiшi протеїну, буферного
електролiту i простої солi у водi при pH = 6.8 (фосфатний буфер) i pH = 4.6 (ацетатний буфер). Ми показуємо, що додавання буферного електролiту вище Tbuffer = 0.6 моль дм⁻³ не впливає на значення Tcloud.
Однак, при замiнi певної кiлькостi буферного електролiту iншою сiллю, тримаючи постiйною повну iонну
мiцнiсть, ми можемо суттєво змiнити температуру точки хмари. Усi солi дестабiлiзують розчин, i величина
ефекту залежить вiд природи солi. Експериментальнi результати аналiзуються в рамках однокомпонентної моделi, яка розглядає взаємодiю протеїн-протеїн як сильно направлену та короткодiючу. Ми використовуємо цей пiдхiд для передбачення других вiрiальних коефiцiєнтiв та фазових дiаграм рiдина-рiдина
при умовах, коли Tcloud визначається експериментально.